UPAYA GURU DALAM MENGATASI KESULITAN CALISTUNG PADA PESERTA DIDIK DI MADRASAH IBTIDAIYAH ROUDLOTUL JANNAH JABUNG MALANG - Amalia Baroroh; Rosichin Mansur; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Based on the results of temporary observations conducted at MI Roudlotul Jannah Jabung Malang which generally have students, it is difficult to understand learning even in reading, writing and counting. What should have been practiced in the Early Childhood and Child-Right Education school so that when students enter Ibtidaiyah Elementary School or Madrasah have the skills to read, write, and count smoothly. Likewise with grade 1 students at MI Roudlotul Jannah Jabung Malang initially when there were many students who had not been fluent in reading, writing and counting. Even though they have graduated from Early Childhood Education and Kindergarten. Keywords: Teacher, Difficulty learning, Calistung, Students.